Molecular detection of Bartonella species in wild small mammals in western Yunnan Province, China - Luo, Yun-Yan; Yu, Dan; Zhang, Hong-Ze; Liu, Zheng-Xiang; Hong, Ru-Dan; Hong, Mei; Ai, Zhi-Qiong; Zhu, Jun-Jie; Yin, Jia-Xiang (Frontiers in Veterinary Science, 2023)
Background: Small mammals serve as the main reservoir for Bartonella and as a proxy indicator of the potential risk of Bartonella transmission from nature to humans. They offer a valuable early warning for human infection. Nevertheless, geographical variations in the impact of the host on the occurrence of Bartonella infection are underestimated. This study was designed to investigate the infection characteristics of Bartonella and explore its species diversity in wild small mammals in western Yunnan Province, China. Methods: Wild small mammals were captured from Yulong, Jianchuan, and Lianghe counties in western Yunnan Province between 2015 and 2016.Real-time quantitative PCR (qPCR) was used to detect Bartonella infection, and the Bartonella species were identified by phylogenetic analysis. The factors associated with Bartonella infection in small mammals were analyzed by the Chi-square Test.The prevalence of Bartonella in small mammals was 47.85% (768/1605).Lianghe County had the highest Bartonella infection rate, with 56.27% of the samples tested positive, followed by a rate of 50.91% was tested in Yulong County, and 39.97% in Jianchuan County (p <0.001). Bartonella was detected positive in a total 25 small mammal species, with infection rates ranging from 2.17% to 100%. Niviventer fulvescens had the highest Bartonella infection rate. In comparison with the dominant small mammal species, Eothenomys mileyus had the lowest Bartonella infection rate than that in Apodemus chevrieri, Rattus tanezumi, and Apodemus draco (p<0.001).Male small mammals had a higher infection rate than females (p<0.05). The prevalence of Bartonella in small mammals during the summer season was higher compared to the other three seasons (p<0.001). Woodland landscape had the highest Bartonella infection rate (p<0.001). Bartonella rochalimae, B. japonica, B. tribocorum, B. washoensis, B. sylvatica, and B. rattimassiliensis were obtained from infected small mammals. Conclusion: This study showed a high prevalence of Bartonella was detected with various Bartonella species in small mammals in Yulong, Jianchuan, and Lianghe counties of western Yunnan Province. These findings hold significant scientific clues, providing valuable reference points for further research of Bartonella natural foci in Yunnan or other analogues environments.